Effects of paternal obesity on maternal-neonatal outcomes and long-term prognosis in adolescents - Lin, Yingying; Chen, Zhiwei; Qian, Qinfang; Wang, Yanxia; Xiu, Xiaoyan; Ou, Ping; Fang, Jiaoning; Li, Guobo (Frontiers in Endocrinology, 2023)
Objective: This study aimed to evaluate whether paternal body mass index (BMI) before pregnancy was a risk factor for maternal-neonatal outcomes and long-term prognosis in offspring. Methods: This study included 29,518 participants from eight cities in Fujian, China using a stratified cluster random sampling method from May to September 2019. They were divided into four groups based on paternal BMI. The relationship of maternal-neonatal outcomes and long-term prognosis in offspring between different paternal BMI groups chi-square test and univariate logistic regression. Results: The incidences of hypertensive disorder complicating pregnancy (HDCP), cesarean delivery, gestational weight gain (GWG) over guideline, and macrosomia were significantly higher than in the paternal overweight and obesity group. Importantly, this study demonstrated that the incidence of asthma, hand-foot-and-mouth disease (HFMD), anemia, dental caries, and obesity of adolescents in paternal obesity increased. Logistic regression furthermore confirms that paternal obesity is a risk factor for HDCP (OR=2.16 (1.71-2.73), a cesarean delivery (OR=1.23 (1.04-1.53), SGA (OR=1.17 (0.99-1.40), macrosomia (OR=1.52 (1.13-1.84). It caused some poor long-term prognosis in adolescents, including asthma (OR=1.58 (1.21-2.06), HFMD (OR=1.28 (1.01-1.78), anemia (OR=1.46 (0.95-1.89), dental caries (OR=1.76 (1.04-2.07) and obesity (OR=1.60 (1.02-2.31). Conclusions: Paternal obesity is a risk factor for adverse maternal-neonatal outcomes and poor long-term prognosis in adolescents. It suggested that men need to pay more attention to weight management in preconception care to reduce the adverse effects on pregnancy complications and the health of their offspring.